The level of accessibility in the Recreation Park Area at Taman Tengku Anis Pasir Mas Kelantan / Nur Arisya Athirah Abdul Ilah - Abdul Ilah, Nur Arisya Athirah (2021)
The development of recreational parks has become a significant concern in today's society. This is because the community now recognises the value of recreational amenities. Furthermore, in accordance with the government's proposal to develop a society that is healthy, active, and caring. The purpose of preparing this study of recreational areas is to gain a true image of the situation and identify the issues that exist in terms of recreational area accessibility as well as provide a proposed plan to develop the area. To achieve this goal, all aspects need to be known whether in terms of theory, concept, problem and potential of the study area. The research was carried out using observation and secondary data. As a result of the analysis conducted, it was found that the recreational park in Taman Tengku Anis Pasir Mas could not fully meet the needs of visitors. The provision of recreational areas that meet the needs of users will be able to attract visitors. Overall, the development of this recreational area can have a positive impact on the development of the environment. With the findings that have been identified, then proposals are proposed to overcome the problems in the study area. With the maintenance and management will determine whether or not the recreation area is successful as an active recreation area.